Petrogenesis and tectonic setting of the early Mesozoic Xitian granitic pluton in the middle Qin-Hang Belt, South China: Constraints from zircon U–Pb ages and bulk-rock trace element and Sr–Nd–Pb isotopic compositions - Wu, Qianhong; Cao, Jingya; Kong, Hua; Shao, Yongjun; Li, Huan; Xi, Xiaoshuang; Deng, Xuantong (Journal of Asian earth sciences, 2016)
•The Indonisian Xitian pluton were formed in Ca. 223Ma–229Ma.•Xitian granites are highly fractionated S-type granites.•These granites were mainly derived from partial melting of Mesoproterozoic-Paleoproterozoic meta-basement of the South China Block.•These granites were formed in an extensional setting. The Xitian pluton in southeast Hunan province is one of the early Mesozoic (Indosinian) granitic plutons in the South China Block. It is composed of biotite adamellite with K-feldspar megacrysts, biotite adamellite, and biotite granite that have U–Pb zircon ages of 229.9±1.4Ma, 223.6±1.3Ma, and 224.0±1.4Ma, respectively. The Indosinian granitoids in the Xitian pluton belong to S-type granites, with highly radiogenic initial 87Sr/86Sr ratios (0.71397–0.71910), negative εNd(t) values ranging from −10.1 to −9.4, and old Nd model ages (1858–1764Ma). They are enriched in radiogenic Pb isotopes, with (206Pb/204Pb)t ranging from 18.130 to 18.903, (207Pb/204Pb)t from 15.652 to 15.722, and (208Pb/204Pb)t from 38.436 to 39.037, respectively. These features indicate that the granitoidswithin the Xitian pluton were formed from magmas generated by remelting of metapelite and metapsammite of the Paleoproterozoic metamorphic basement at temperatures of ca. 800°C, with low oxygen fugacity. The Sr–Nd isotopic compositions of the rocks from Xitian pluton indicate that the granitic magmas were mixed with less than 10% mantle-derived magmas. We suggest that the Xitian pluton was emplaced in an extensional tectonic setting related to release of compressional stresses within the thickened crust during the early Mesozoic.